Low-intensity cognitive behavioral therapy for social anxiety disorder in individuals experiencing grief - Avramchuk , Oleksandr Serhiyovych; Nizdran , Oleksandra Аndriivna; Blozva , Pavlo Іhorovych (Insight: the psychological dimensions of society, 2023)
The purpose of the research is to obtain confirming data on the reduction of symptom severity and levels of psychosocial dysfunction under the influence of low-intensity cognitive-behavioral therapy (CBT)techniques among individuals with social anxiety disorder during the grieving period. Methods: The Mini-International Neuropsychiatric Interview was used to assess mental health problems during the initial diagnostic interview. Measurements of key indicators were carried out using methods such as Social Phobia Inventory (SPIN); the level of psychosocial distress due to loss, and the risk of complicated grief, comorbid conditions such as the level of generalized anxiety (GAD-7); the severity of emotional avoidance(AAQ-II); and the general level of distress in daily and work activities were measured using the W&SAS scale. Results: The results of changes in mental state before and after the program demonstrated significant improvements in the indicators of generalized anxiety, the severity of comorbid depressive symptoms, the impact of traumatic experiences, the reduction of emotional avoidance, and associated psychosocial disorders. However, there was no statistically significant difference in the reduction of social phobia symptoms and distress associated with the experience of loss. One month after completing the program, the participants used breathing control strategies (including mindfulness practices) and cognitive restructuring more frequently in situations involving social avoidance or joint activities to manage their distress. After six months of completing the program, the most frequently mentioned responses from the participants were related to coping and working with dysfunctional beliefs about the consequences of events and social situations that prevented the activation of defensive behavior through avoidance. Conclusions. An individual low-intensity online psychosocial support program based on CBT for individuals suffering from social anxiety disorder and experiencing complex life circumstances (such as the loss of a loved one) has demonstrated a reduction in psychosocial distress and severity of mental symptoms. It has been found that satisfying social needs and providing corrective experiences in a safe social space for grieving can promote psychological well-being and serve as protective factors against exacerbations of mental health problems.
Keywords: Array